UPAYA MENINGKATKAN PEMBELAJARAN KASTI MELALUI PERMAINAN MEMBURU KIJANG PADA SISWA KELAS IV SD NEGERI 02 LEGOKCLILE KEC. BOJONG KAB. PEKALONGAN TAHUN AJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the enhancement of learning through play baseball game hunt deer in grade IV Elementary School District 02 Legokclile Pekalongan Olean School Year 2012/2013. The research was conducted in four stages, each stage including planning, action, observation, and reflection using the method of classroom action research . The subjects of this study were fourth grade students Negeri02 Legokclile second semester of the school year 2012/2013 amounted to 30 students. The instrument used to collect data in this study is the observation sheets, questionnaires and tests students' performance. The results are based on analysis of the percentage of prasiklus average value of 73.1 with a percentage of 40% and then headed to the first cycle increased with an average value of 70% and 75.6 percentage kesiklus II increased with an average value of 78.1 percentage 80 , 33% with this assessment of the success indicators of success expected 80%.The conclusions of this study indicate that deer hunting games can improve learning outcomes in learning baseball in fourth grade siaswa State 02 Legokclile district. Olean district. Pekalongan.